The relationship code : deciphering genetic and social influences on adolescent development - Reiss, David; Neiderhiser, Jenae M.; Hetherington, E. Mavis; Plomin, Robert (Cambridge, Mass. : Harvard University Press, 2000)
Introduction: Reconciling social and genetic influences on adolescent development
Part 1: Logical tools for analyzing adolescent development
Relationships and adolescent development
Genetic influences on development
Genetic analysis of adolescent development
Studying adolescent siblings and their families
Part 2: Genes and relationships: Thesis, antithesis, synthesis
Thesis I: A theory of adolescents' shared and nonshared family relationships
Thesis II: Major findings on adolescents' family relationships
Antithesis I: Influences on stability and change in adolescent adjustment
Antithesis II: Influences on stability and change in adolescents' families
Antithesis III: Linking family relationships and adolescent development
Synthesis I: Genetic influences on change in family relationships and adolescent development
Synthesis II: The relationship code
Synthesis III: Genetically informed portrayals of adolescents and their families
Epilogue: The family
Appendix A: Explanation of methods for data presented in Chapters 8 through 13
Appendix B: Explanation of results
Appendix C: Additional genetic analyses
Bibliografija
Kazalo
Keywords: razvoj adolescenata; bihevioralna genetika